2016
DOI: 10.3389/fphar.2016.00258
|View full text |Cite
|
Sign up to set email alerts
|

Head to Head Comparison of Short-Term Treatment with the NAD+ Precursor Nicotinamide Mononucleotide (NMN) and 6 Weeks of Exercise in Obese Female Mice

Abstract: Obesity is well known to be a major cause of several chronic metabolic diseases, which can be partially counteracted by exercise. This is due, in part, to an upregulation of mitochondrial activity through increased nicotinamide adenine dinucleotide (NAD+). Recent studies have shown that NAD+ levels can be increased by using the NAD+ precursor, nicotinamide mononucleotide (NMN) leading to the suggestion that NMN could be a useful intervention in diet related metabolic disorders. In this study we compared the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 55 publications
7
96
5
Order By: Relevance
“…Mounting evidence supports the notion that enhancing tissue NAD + availability has beneficial effects on metabolic health in the context of metabolic disease and physiological decline [22], [23], [47], [48], [49]. The leading method to accomplish NAD + augmentation is through dietary supplementation with NR and NMN.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence supports the notion that enhancing tissue NAD + availability has beneficial effects on metabolic health in the context of metabolic disease and physiological decline [22], [23], [47], [48], [49]. The leading method to accomplish NAD + augmentation is through dietary supplementation with NR and NMN.…”
Section: Discussionmentioning
confidence: 99%
“…The mice that died before the 24 h time point were included only in the experiment of post 24 h mortality rate; these mice were not included in the other analyses. In previous studies, NMN was administered to mice at doses of~1 00 mg·kg À1 (Park et al, 2016) to 500 mg·kg À1 (Long et al, 2015;Uddin et al, 2016). However, most studies applied the dose of 300 mg·kg À1 Yoshino et al, 2011;Zhang et al, 2011;Stein and Imai, 2014;Zhao et al, 2015b;de Picciotto et al, 2016;Wei et al, 2017); therefore, we used 300 mg·kg À1 in this study.…”
Section: Delayed Tpa Treatment and Nmn Administrationmentioning
confidence: 99%
“…Depletion of intracellular NAD is a common pathway in many pathophysiological events, including ageing, metabolic disorders and cerebral ischaemia (Yang et al, 2002;Massudi et al, 2012;Zhang et al, 2016;Zhou et al, 2016;Wang et al, 2016a). The administration of nicotinamide mononucleotide (NMN) or nicotinamide riboside, two NAD precursors, as a supplement is able to enhance NAD levels and is used to treat high-fat-induced obesity/fatty liver (Yoshino et al, 2011;Uddin et al, 2016;Zhou et al, 2016). We and other groups have demonstrated that NMN protects against post-ischaemic NAD degradation and decreases brain damage after cerebral ischaemia Zhao et al, 2014;Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Age-associated arterial dysfunction can be rescued and returned to young mice levels after supplementation with nicotinamide mononucleotide (NMN), a key NAD + intermediate capable to increase SIRT1 activity (de Picciotto et al, 2016). Intraperitoneal administration of NMN significantly increases NAD + levels both in liver and muscle of diet-induced obese mice, but leads to improvement in glucose tolerance and the recovery in citrate synthase activity only in the liver (Uddin et al, 2016). Interestingly, exercise allows the restoration of citrate synthase activity in muscle of obese mice on a high-fat diet indicating that NMN exerts tissue-specific effect in vivo (Uddin et al, 2016).…”
Section: Metabolic Sensors In Agingmentioning
confidence: 99%
“…Intraperitoneal administration of NMN significantly increases NAD + levels both in liver and muscle of diet-induced obese mice, but leads to improvement in glucose tolerance and the recovery in citrate synthase activity only in the liver (Uddin et al, 2016). Interestingly, exercise allows the restoration of citrate synthase activity in muscle of obese mice on a high-fat diet indicating that NMN exerts tissue-specific effect in vivo (Uddin et al, 2016). …”
Section: Metabolic Sensors In Agingmentioning
confidence: 99%